1971
DOI: 10.1136/jcp.24.8.677
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscope study of PNH red cells and AET-treated normal red cells (PNH-like cells)

Abstract: SYNOPSISThe morphology of red cells damaged by 2-aminoethylisothiouronium bromide (AET) has been compared to that of PNH cells by transmission and scanning electron microscopy. The main features of the effect of AET as demonstrated by the scanning electron microscope were spherical and deformed cells, with surface craters and relatively large pits. The transmission electron microscope revealed loss of surface structure, an unusual amount of irregularly shaped electrondense material and fine pits in the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Thus craters, pits and protuberances do not seem to be specific for PNH red cells. Stomatocytic or sphero-stomatocytic shape changes of AET-treated red cells observed in this study were compatible with that reported by Lewis et al (1971), and suggest marked alteration of membrane structure. However, GSH-treated red cells all of which were considered to have obtained PNH-like characteristics, showed no significant morphologic abnormalities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus craters, pits and protuberances do not seem to be specific for PNH red cells. Stomatocytic or sphero-stomatocytic shape changes of AET-treated red cells observed in this study were compatible with that reported by Lewis et al (1971), and suggest marked alteration of membrane structure. However, GSH-treated red cells all of which were considered to have obtained PNH-like characteristics, showed no significant morphologic abnormalities.…”
Section: Discussionsupporting
confidence: 92%
“…Some authors have reported that the craters, pits and protuberances are found in PNH red cells by scanning electron microscopy (Lambertenghi et al 1970; Lewis et al 1971). These morphologic abnormalities were not seen in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Present SEM images of PNH red cells resulted quite similar to those previously reported [6,8], although the past studies had not paid too much attention to the presence of swollen cells in the PNH erythrocyte pool. Likewise, any relationship between percentage of PNH abnormal erythrocytes and severity of the haemolytic disorder was strictly refused [6,8].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, re cent scanning electron microscope (SEM) studies [6,8] reported the pres ence in PNH erythrocytes of (a) marked variations in cell size, due to the high reticulocyte counts; (b) numerous thalassaemia-like target cells, with a prominent protuberance raising from their concavity; and (c) pits and deep craters, on the surface of most deformed elements. However, no cor relation could be stated between frequency of altered erythrocytes and se verity of the haemolytic disorder [6,8], By means of the SEM, the ideal tool for investigating cell surfaces, in the present study the problem of PNH erythrocytes has again been consi dered, in the attempt to evidence nature and degree of red cell alterations, as well as the occurrence of a possible relationship between such deforma tions and severity of the haemolytic disorder. Such problem may be tackled (a) by inducing PNH red cell haemolysis with mechanisms sim ilar to those occurring in vivo, (b) by testing different complement-sen sitivity of red cells with progressively decreasing serum dilutions, and then (c) by evidencing with SEM the features of the cells which survive in any dilution.…”
mentioning
confidence: 99%
“…21 Moreover, published studies have shown that AET treatment mimics PNH biochemically, serologically, and by electron microscopy. [22][23][24][25] We expanded on the current knowledge about the regulation of complement activation by demonstrating low or absent MIRL antigen expression with or without DAF predispose RBCs to hemolysis. Our study showed that a low titer anti-A isoagglutinin, which normally failed to activate complement in vitro with healthy RBCs, can potentially cause significant hemolysis resulting from RBC-related factors.…”
Section: Discussionmentioning
confidence: 99%